The Status of Local Examination as a Consideration For Judges in the Settlement of Civil Disputes in the Tabanan District Court - Virgayanti, Ni Luh Gede Intan; Nurianto, Nurianto; Nurindahwati, Zuhro (Westscience Press, 2025)
Local examination is one of the procedural instruments in civil procedural law that serves as a means for judges to directly observe the disputed object. Although it is not formally classified as evidence under Article 1866 of the Indonesian Civil Code, local examination holds significant value in supporting the judge's conviction regarding material truth. This study aims to analyze the role of local examination and identify the obstacles in its implementation at the Tabanan District Court. The research method used is normative legal research with a statutory, conceptual, and case approach. The results show that local examination plays a vital role in the evidentiary process, especially in land disputes, and often becomes a key judicial consideration in civil case decisions. However, its implementation still faces several challenges, including limited budget, geographical access difficulties, and a lack of legal understanding among the litigating parties. Therefore, there is a need for regulatory reinforcement, increased operational support, and public legal education to ensure that local examination is carried out optimally in upholding justice and legal certainty.